Pengaruh Tipe Kepribadian Dan Locus Of Control Terhadap Kinerja Karyawan Di Cafe Kopi Studio24 Kota Malang - Tafta Suharto Risky; Abd Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of personality type and locus of control on employee performance simultaneously or partially. The research conducted at Cafe Kopi Studio24 Kota Malang uses a type of survey research in which there are 45 populations and the entire population can be used as a sample. Data collection techniques used in this research is by distributing questionnaires. This research method uses multiple rigression analysis using the IBM SPSS STATISTIC 25.0 Program as an analysis tool.Based on the results of the study, it can be concluded that the personality type variable has no effect on the performance of employees at Cafe Kopi Studio24 seen from the results of the multiple rigression analysis test which showed a significance value of 0.423> 0.05.the locus of control variable has a significance value of 0.03 <0.05 which states that the locus of control affects the performance of employees at Cafe Kopi Studio24. Keywords : personality type, locus of control and employee performance